Concern, intention and food waste behaviour: the intention-behaviour gap among households in Kuala - Mohd Nazi, Sarah Ainina; Mat Issa, Zuraini; Abdul Aziz, Saidatul Afzan (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2025)
Household was reported to contribute the most to food waste. Food waste in households is shaped not only by demographic factors, but also by behaviours, intentions and attitudes towards food use and waste. Thus, this study aims to examine the intention–behaviour gap related to food waste practices among households in Kuala Lumpur, Malaysia. The study will investigate the relationship between concern about the environmental and social implications of food waste and individuals’ intention to reduce waste and their actual waste behaviour. Using a stratified random sampling approach based on residential accommodation types and income classifications, an online questionnaire was distributed to residents’ WhatsApp and Facebook groups. A total of 302 households completed the survey. The collected data were analysed using SPSS version 26. Pearson’s correlation analysis was conducted to determine relationships between concern about food waste implications, intention not to waste food, and selfreported food waste behaviour. A moderate and significant positive correlation was found between concern about the implications of food waste and the intention not to waste (r = 0.575, p < 0.001). However, neither concern about food waste implications (r = 0.104, p = 0.071) nor intention not to waste food (r = -0.041, p = 0.473) showed significant associations with actual household food waste. These findings reveal a substantial gap between pro-environmental intentions and daily practices. Hence, the study highlights the need for targeted behavioural interventions and supportive policies that go beyond raising awareness to bridge this gap. Insights from this study can inform urban waste reduction strategies, policy development, and public education campaigns in Malaysia and similar urban contexts.